Professional risks when carrying out cytoreductive surgery for peritoneal malignancy with hyperthermic intraperitoneal chemotherapy (HIPEC): A French multicentric survey. Issue 10 (October 2015) - Ferron, G.; Simon, L.; Guyon, F.; Glehen, O.; Goere, D.; Elias, D.; Pocard, M.; Gladieff, L.; Bereder, J.M.; Brigand, C.; Classe, J.M.; Guilloit, J.M.; et al.
Abstract Background Over the last two decades, many surgical teams have developed programs to treat peritoneal carcinomatosis with extensive cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC). Currently, there are no specific recommendations for HIPEC procedures concerning environmental contamination risk management, personal protective equipment (PPE), or occupational health supervision. Methods A survey of the institutional practices among all French teams currently performing HIPEC procedures was carried out via the French network for the treatment of rare peritoneal malignancies (RENAPE). Results Thirty three surgical teams responded, 14 (42.4%) which reported more than 10 years of HIPEC experience. Some practices were widespread, such as using HIPEC machine approved by the European Community (100%), individualized or centralized smoke evacuation (81.8%), "open" abdominal coverage during perfusion (75.8%), and maintaining the same surgeon throughout the procedure (69.7%). Others were more heterogeneous, including laminar flow air circulation (54.5%) and the provision of safety protocols in the event of perfusate spills (51.5%). The use of specialized personal protective equipment is ubiquitous (93.9%) but widely variable between programs. Conclusion Protocols regarding cytoreductive surgery/HIPEC and the associated professional risks in France lack standardization and should be established.